2010
DOI: 10.1089/pho.2009.2484
|View full text |Cite
|
Sign up to set email alerts
|

Combination 830-nm and 633-nm Light-Emitting Diode Phototherapy Shows Promise in the Treatment of Recalcitrant Psoriasis: Preliminary Findings

Abstract: The antiinflammatory effects of LED energy at 830 nm and 633 nm have been well documented, as has their use in wound healing. LED phototherapy is easy to apply, pain free and side-effect free, and is well tolerated by patients of all skin types. The promising results of this preliminary study warrant a proper controlled double-blind study with a larger patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…PBM has been used for psoriasis because of its anti-inflammatory effects, which is a different approach from UV phototherapy which tends to kill circulating T-cells. Ablon [99] tested PBM using LEDs (830 nm, 60 J/cm 2 and 633 nm, 126 J/cm 2 ) in two 20-min sessions over 4 or 5 weeks, with 48 h between sessions in 9 patients with chronic treatment-resistant psoriasis. Clearance rates at the end of the follow-up period ranged from 60% to 100%.…”
Section: Clinical Applications Of Pbm For Inflammationmentioning
confidence: 99%
“…PBM has been used for psoriasis because of its anti-inflammatory effects, which is a different approach from UV phototherapy which tends to kill circulating T-cells. Ablon [99] tested PBM using LEDs (830 nm, 60 J/cm 2 and 633 nm, 126 J/cm 2 ) in two 20-min sessions over 4 or 5 weeks, with 48 h between sessions in 9 patients with chronic treatment-resistant psoriasis. Clearance rates at the end of the follow-up period ranged from 60% to 100%.…”
Section: Clinical Applications Of Pbm For Inflammationmentioning
confidence: 99%
“…Despite the promising cell-biostimulatory results obtained with phototherapy, such as modulation of tissue inflammation (15) and stimulation of fibroblast cell metabolism, odontoblast-like cells, and human pulp cells (10,11,(16)(17)(18), information about the effects of infrared LED on the metabolism and mineralization ability of stem cells from human exfoliated deciduous teeth is scant. Therefore, the aim of this study was to evaluate the effects of 850-nm LED irradiation on cultured stem cells from human exfoliated deciduous teeth (SHEDs) at different energy densities.…”
Section: Introductionmentioning
confidence: 99%
“…). Studies have demonstrated that light at the wavelength in the infrared region could exert an anti‐inflammatory effect (Ablon ), increase cell metabolism (Vinck et al . , Oliveira et al .…”
Section: Introductionmentioning
confidence: 99%